Consensus molecular subtypes (CMS) in metastatic colorectal cancer - Reberšek, Martina (Radiology and oncology (Ljubljana), 2020)
Colorectal cancer (CRC) is one of the most common types of cancer in the world. Metastatic disease is still incurable in most of these patients, but the survival rate has improved by treatment with novel systemic chemotherapy and targeted therapy in combination with surgery. New knowledge of its complex heterogeneity in terms of genetics, epigenetics, transcriptomics and microenvironment, including prognostic and clinical characteristics, led to its classification into various molecular subtypes of metastatic CRC, called consensus molecular subtypes (CMS). The CMS classification thus enables the medical oncologists to adjust the treatment from case to case. They can determine which type of systemic chemotherapy or targeted therapy is best suited to a specific patient, what dosages are needed and in what order. Conclusions. CMS in metastatic CRC are the new tool to include the knowledge of molecular factors, tumour stroma and signalling pathways for personalized, patient-orientated systemic treatment in precision medicine.
Keywords: biološki označevalci; kolorektalni rak; metastaze